Dilute iota- and kappa-Carrageenan solutions with high viscosities in high salinity brines - Iglauer, Stefan; Wu, Y.; Shuler, P.; Tang, Y.; Goddard, W. (Elsevier BV, 2011)
We evaluated the rheological characteristics of ι- and κ-Carrageenan in aqueous solutions. Viscosities strongly increased with increasing polymer concentration or salinity. Monovalent Na+ cations were more effective in increasing viscosity than divalent Ca2+ cations. A more complex brine containing Na+, Mg2+ and Ca2+ cations also showed high viscosities at a high salinity. We observed shear thinning behavior for these polysaccharide solutions. We explain these rheological phenomena with molecular processes, specifically the conformation change of the ι-Carrageenan from random coil to double helix. In the context of enhanced oil recovery, ι-Carrageenan solutions can reach much higher viscosities at high salinities than standard polyacrylamide solutions. Moreover, Carrageenans are renewable, nontoxic, green substances.